Special fluorine-containing soluble polyimide adhesive for lithium battery as well as preparation method and application of special fluorine-containing soluble polyimide adhesive

By using fluorine-containing soluble polyimide adhesive in lithium-ion batteries, the problem of electrode structure damage caused by volume changes in silicon negative electrode materials is solved, and higher battery rate performance and stability are achieved.

CN119463793APending Publication Date: 2025-02-18CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411533706.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The silicon negative electrode material in lithium-ion batteries causes damage to the electrode structure and failure of bonding due to volume expansion and contraction, which in turn causes capacity attenuation and shorten cycle life.

Method used

A fluorine-containing soluble polyimide adhesive is designed, with the main chain containing -Si-O-Si-structure, which enhances chemical compatibility with silicon particles and forms a more stable interface bond.

Benefits of technology

It improves the bonding characteristics and stability of electrode materials, enhances the rate performance of lithium batteries, and provides a high stability, high capacity and suitable for large-scale production of silicon negative electrode adhesive solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463793A_ABST
    Figure CN119463793A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion batteries, in particular to a fluorine-containing soluble polyimide adhesive special for a lithium battery and a preparation method and application of the fluorine-containing soluble polyimide adhesive. The fluorine-containing polyimide is prepared by reacting dianhydride and diamine, the dianhydride comprises 3, 3 ', 4, 4'-benzophenone tetracarboxylic dianhydride, the diamine comprises 4, 4 '-bis (4-amino-2-trifluoromethylphenoxy) biphenyl and 1, 3-bis (3-aminopropyl)-1, 1, 3, 3-tetramethyldisiloxane, the structure of the fluorine-containing polyimide in the adhesive is as shown in a formula I: # imgabs0 #, and the fluorine-containing polyimide in the adhesive is fluorine-containing polyimide. The groups A and B are independently selected from # imgabs 1 # or # imgabs 2 #, and A is different from B. The adhesive is applied to a lithium ion battery, especially a silicon negative electrode lithium ion battery, shows excellent rate capability and adhesive performance, and has a good industrial prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a novel adhesive based on polyimide (PI), specifically a fluorine-containing soluble polyimide adhesive specially used for lithium batteries, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have become the core power source for electric vehicles, portable electronic devices and energy storage systems due to their excellent energy density, long cycle life and high power output. However, as the requirements for battery performance in these applications continue to increase, the energy density of existing lithium-ion batteries is approaching its theoretical limit. In order to further improve the energy density of batteries, researchers are actively exploring new high-capacity electrode materials.

[0003] At present, the negative electrode of commercial lithium-ion batteries mainly uses graphite. Although graphite has good conductivity and stable cycle life, its theoretical capacity is only 372 mAh / g, which is difficult to meet the future demand for high-energy density batteries. In contrast, silicon as a negative electrode material has an extremely high theoretical specific capacity (about 4200 mAh / g), which is more than ten times that of graphite. In addition, silicon is abundant in resources and low in cost, making it an ideal negative electrode material for the next generation of high-energy density lithium-ion batteries.

[0004] However, silicon anodes still face many challenges in practical applications. The biggest problem is that silicon will expand and shrink by more than 300% during lithium insertion and extraction, resulting in silicon particle rupture, electrode structure damage and bonding failure, which will cause rapid capacity decay and shortened cycle life. In addition, an unstable solid electrolyte interface film (SEI) is easily formed on the silicon surface, further reducing battery performance.

[0005] To solve these problems, researchers have proposed a variety of strategies, such as designing nanostructures, preparing composite materials, and developing high-performance binders. The binder is not only responsible for tightly combining the active material with the conductive agent in the electrode, but also provides mechanical support to alleviate the volume change of the electrode material during the cycle. Traditional binders such as polyvinylidene fluoride (PVDF), although chemically stable, have poor mechanical properties and are difficult to cope with the volume change of silicon negative electrode materials.

[0006] Polyimide (PI) is a polymer material with excellent performance, widely used in aerospace, electrical and electronic, chemical and other fields. The aromatic ring and imide group in the molecular structure of polyimide give it excellent mechanical strength, heat resistance and chemical stability. These characteristics and its own certain bonding ability meet the needs of silicon negative electrode lithium battery adhesives, but traditional polyimide adhesives are mostly insoluble materials, and the high-temperature dehydration step in the preparation process will produce larger pores, affecting the bonding performance. Summary of the invention

[0007] The present invention aims at the technical problems encountered in the practical application of high energy density lithium ion batteries, and designs a fluorine-containing soluble polyimide adhesive material. The main chain of the adhesive material contains a -Si-O-Si- structure. The presence of the silicon-oxygen bond (-Si-O-Si-) makes the polyimide material more chemically compatible with silicon particles, which helps to form a more stable interface bonding. The electrode material prepared by using the fluorine-containing soluble polyimide adhesive material has high bonding properties and high stability. The assembled lithium battery shows a higher rate. The adhesive material is an effective solution for silicon negative electrode adhesives with high stability and high capacity and suitable for large-scale production.

[0008] The first object of the present invention is to provide a fluorine-containing soluble polyimide adhesive for lithium batteries, wherein the fluorine-containing polyimide is prepared by reacting a dianhydride with a diamine, wherein the dianhydride includes 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), and the diamine includes 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (6FBAB) and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane (2SON), wherein the structure of the fluorine-containing polyimide is as shown in Formula I: , Wherein, groups A and B are independently selected from or , and A and B are different.

[0009] Preferably, the dianhydride further comprises other dianhydrides, and the diamine further comprises other diamines.

[0010] More preferably, the other dianhydride is at least one selected from 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), polyphthalic anhydride (PMDA), 4,4'-oxydiphthalic anhydride (ODPA) and 4,4'-hexafluoroisopropylphthalic anhydride (6FDA).

[0011] More preferably, the other diamine is at least one selected from 4,4'-diaminodiphenyl ether (ODA), p-phenylenediamine (PDA) and 2,2'-bis(trifluoromethyl)diaminobenzene (TFMB).

[0012] In some embodiments, the dianhydride is 4,4'-hexafluoroisopropylphthalic anhydride (6FDA) and 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), and the diamine is 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (6FBAB), 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane (2SON) and 4,4'-diaminodiphenyl ether (ODA).

[0013] In some embodiments, the dianhydride is 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) and 4,4'-oxydiphthalic anhydride (ODPA), and the diamine is 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (6FBAB), 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane (2SON), and 2,2'-bis(trifluoromethyl)diamino (TFMB).

[0014] Preferably, the molar percentage of the structure of formula I in the fluorine-containing polyimide binder is 70-100%.

[0015] Preferably, the binder further comprises an inorganic material, and the inorganic material is selected from inorganic fibers, preferably ilex fibers.

[0016] Further preferably, the mass ratio of the inorganic material to the fluorinated polyimide is 1:8-12.

[0017] The second object of the present invention relates to a method for preparing the above-mentioned fluorine-containing soluble polyimide binder, the preparation method comprising the following steps: (1) Adding dianhydride and diamine to a non-protonic polar solvent to prepare a polyamic acid resin solution by polycondensation reaction; (2) After the polymerization is completed, a catalyst and a dehydrating agent are added, and the reaction is continued by stirring to obtain a sol; (3) Pour the sol into anhydrous ethanol for precipitation.

[0018] Preferably, the aprotic polar solvent in step (1) is selected from at least one of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP) and N,N-dimethylacetamide (DMAc).

[0019] Preferably, the reaction temperature in step (1) is room temperature, preferably 25°C; the reaction time is 12-24 h, preferably 16 h; and the rotation speed is 50-300 r / min, preferably 280 r / min.

[0020] Preferably, the catalyst in step (2) is at least one selected from pyridine, isoquinoline and picoline.

[0021] Preferably, the dehydrating agent in step (2) is acetic anhydride.

[0022] Preferably, the reaction time in step (2) is 12-24 h, preferably 16 h; the rotation speed is 50-300 r / min, preferably 280 r / min.

[0023] The third object of the present invention relates to the application of the above-mentioned fluorine-containing soluble polyimide binder in the field of lithium-ion batteries.

[0024] Preferably, the lithium-ion battery is a silicon negative electrode lithium-ion battery.

[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The main chain of the fluorine-containing soluble polyimide adhesive material of the present invention contains a -Si-O-Si- structure. The presence of the silicon-oxygen bond (-Si-O-Si-) makes the polyimide material more chemically compatible with silicon particles, which helps to form a more stable interface bond; (2) The electrode material prepared by using the fluorine-containing soluble polyimide adhesive of the present invention has high bonding properties and high stability, and the assembled lithium battery exhibits a higher rate. The present invention is an effective solution for silicon negative electrode binders with high stability, high capacity and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the battery rate performance diagram of the prepared PI binder material. DETAILED DESCRIPTION

[0027] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0028] The methods are conventional methods unless otherwise specified. The materials are available from public commercial sources unless otherwise specified.

[0029] The performance evaluation method of the fluorine-containing soluble polyimide (PI) binder material obtained in the following examples is as follows: Evaluation method of electrochemical properties of PI binder materials: The rate performance test was determined using the Blue Electric Test System CT3002A. The test conditions were 5 cycles of charge and discharge at current densities of 0.1 C, 0.5 C, 1 C, 2 C, and 5 C, respectively.

[0030] Evaluation method for the peeling performance of PI adhesive materials: stick a 5 cm × 2 cm 3M tape on the dried battery electrode, and connect the other end of the tape to a tensile testing machine so that the tape peels off the slurry on the electrode surface at a constant speed (1 cm / min) at an angle of 180°. The force of the tensile testing machine gradually increases from 0 N until the tape completely falls off the electrode, and the average force during the peeling process is recorded.

[0031] Example 1 Preparation of PI binder material using BTDA and 6FBAB / 2SON 21.417 g of 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (6FBAB) and 12.426 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane (2SON) were weighed and placed in a round-bottom flask. An appropriate amount of DMAc solvent was added to dissolve them under stirring. 32.223 g of 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA) was weighed and added to the above device. The stirring speed was 280 r / min and the reaction time was 16 h. Subsequently, acetic anhydride and pyridine were added to the device, the speed was set unchanged, and stirring was continued for 16 h. After the reaction was completed, the obtained sol was poured into anhydrous ethanol solution for precipitation to obtain a soluble PI binder material.

[0032] Take the prepared PI binder material and dissolve it in the NMP solution to prepare a solution with a PI content of 0.2 g / mL. According to the ratio of active material (Si / C, standard specific capacity 650 mAh / g): conductive agent (Super P): binder (PI) = 5:4:1, take an appropriate amount and put it in a 20 ml small glass bottle, stir it magnetically for 10 hours, and prepare the electrode slurry. Then, use a 150-micron-thick scraper to evenly coat the slurry on the carbon-coated copper foil, put it in a positive vacuum oven and heat it at 120°C for 10 hours to obtain a dry electrode. Then, assemble the battery in a glove box and test the rate performance.

[0033] Rate performance as attached Figure 1 As shown; The peel strength properties of the prepared PI adhesive material are shown in Table 1.

[0034] Example 2: Doping Halloysite Nanotubes in BTDA and 6FBAB / 2SON to Prepare PI Binder Material The preparation method of the PI binder material in Example 2 is the same as that in Example 1, except that after the PI material is dissolved in the NMP solution, 10% of the mass of halloysite nanotubes of PI are added thereto, and the subsequent steps of preparing the electrode plates and assembling the battery are the same, and it is named PI-FSH.

[0035] Rate performance as attached Figure 1 As shown; The peel strength properties of the prepared PI adhesive material are shown in Table 1.

[0036] Example 3: Preparation of polyimide (PI) binder material using 6FDA, BTDA, ODA and 6FBAB 10.0118 g of 4,4'-diaminodiphenyl ether (ODA) and 21.417 g of 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (6FBAB) were weighed and placed in a round-bottom flask. An appropriate amount of DMAc solvent was added to dissolve them under stirring. 22.21 g of 4,4-hexafluoroisopropylphthalic anhydride (6FDA) and 32.223 g of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) were weighed and added to the above device. The stirring paddle speed was 280 r / min and the reaction time was 16 h. Subsequently, acetic anhydride and pyridine were added to the device, the speed setting remained unchanged, and stirring was continued for 16 h. After the reaction, the obtained sol was poured into anhydrous ethanol solution for precipitation to obtain a fluorine-containing soluble PI binder material.

[0037] Take the prepared PI binder material and dissolve it in the NMP solution to prepare a solution with a PI content of 0.2 g / mL. According to the ratio of active material (Si / C, reversible specific capacity 650 mAh / g): conductive agent (Super P): binder (PI) = 5:4:1, take an appropriate amount and put it in a 20 mL small glass bottle, stir it magnetically for 10 hours, and prepare the electrode slurry. Then, use a 150-micron-thick scraper to evenly coat the slurry on the carbon-coated copper foil, put it in a positive vacuum oven and heat it at 120°C for 10 hours to obtain a dry electrode. Then, assemble the battery in a glove box and test the rate performance.

[0038] The peel strength properties of the prepared PI adhesive material are shown in Table 1.

[0039] Example 4: Doping of Halloysite Nanotubes in Polyimide (PI) Binder Materials Prepared from 6FDA, BTDA, ODA, and ODA The preparation method of the PI binder material in Example 4 is the same as that in Example 3, except that after the PI material is dissolved in the NMP solution, 10% of the mass of the PI halloysite nanotubes are added thereto, and the subsequent steps of preparing the electrode sheet and assembling the battery are the same. The peel strength properties of the prepared PI adhesive material are shown in Table 1.

[0040] Example 5: Preparation of polyimide (PI) binder material using ODPA, BTDA, TFMB and 6FBAB 16.0115 g of 2,2'-bis(trifluoromethyl)diamino (TFMB) and 21.417 g of 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (6FBAB) were weighed and placed in a round-bottom flask. An appropriate amount of DMAc solvent was added to dissolve them under stirring. 15.5105 g of 4,4'-oxydiphthalic anhydride (ODPA) and 32.223 g of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) were weighed and added to the above device. The stirring paddle speed was 280 r / min and the reaction time was 16 h. Subsequently, acetic anhydride and pyridine were added to the device, the speed setting remained unchanged, and stirring was continued for 16 h. After the reaction, the obtained sol was poured into anhydrous ethanol solution for precipitation to obtain a fluorine-containing soluble PI binder material.

[0041] Take the prepared PI binder material and dissolve it in the NMP solution to prepare a solution with a PI content of 0.2 g / mL. According to the ratio of active material (Si / C, reversible specific capacity 650 mAh / g): conductive agent (Super P): binder (PI) = 5:4:1, take an appropriate amount and put it in a 20 mL small glass bottle, stir it magnetically for 10 hours, and prepare the electrode slurry. Then, use a 150-micron-thick scraper to evenly coat the slurry on the carbon-coated copper foil, put it in a positive vacuum oven and heat it at 120°C for 10 hours to obtain a dry electrode. Then, assemble the battery in a glove box and test the rate performance.

[0042] The peel strength properties of the prepared PI adhesive material are shown in Table 1.

[0043] Example 6: Doping of Halloysite Nanotubes in Polyimide (PI) Binder Materials Prepared from ODPA, BTDA, TFMB, and 6FBAB The preparation method of the PI binder material in Example 6 is the same as that in Example 5, except that after the PI material is dissolved in the NMP solution, 10% of the mass of the PI halloysite nanotubes are added thereto, and the subsequent steps of preparing the electrode sheet and assembling the battery are the same. The peel strength properties of the prepared PI adhesive material are shown in Table 1.

[0044] Comparative Example 1 Polyvinylidene fluoride (PVDF) as a binder for lithium-ion batteries The polyvinylidene fluoride (PVDF) in Comparative Example 1 is a product produced by Arkema, France. PVDF was dissolved in NMP solution to prepare a solution with a PVDF content of 0.2 g / ml. According to the ratio of active material (Si / C, standard specific capacity 650 mAh / g): conductive agent (Super P): binder (PVDF) = 5:4:1, an appropriate amount was placed in a 20 ml small glass bottle, and magnetic stirring was performed for 10 h to prepare the electrode slurry. The slurry was then evenly coated on the carbon-coated copper foil with a 150-micron-thick scraper, and placed in a positive vacuum oven and heated at 120°C for 10 h to obtain a dry electrode. The battery was then assembled in a glove box to test the rate performance.

[0045] Rate performance as attached Figure 1 As shown; The specific data of peel strength performance are listed in Table 1.

[0046] Comparative Example 2 Carboxymethyl cellulose (CMC) as a binder for lithium-ion batteries The carboxymethyl cellulose (CMC) in comparative example 2 was purchased from Kejingxing Technology Co., Ltd. (Shenzhen). CMC was dissolved in deionized water to prepare a solution with a CMC content of 0.2 g / ml. According to the ratio of active material (Si / C, standard specific capacity 650 mAh / g): conductive agent (Super P): binder (CMC) = 5:4:1, an appropriate amount was placed in a 20 ml small glass bottle, and magnetic stirring was performed for 10 hours to prepare the electrode slurry. The slurry was then evenly coated on the carbon-coated copper foil with a 150-micron-thick scraper, and placed in a positive vacuum oven and heated at 120°C for 10 hours to obtain a dry electrode sheet. The battery was then assembled in a glove box to test the rate performance.

[0047] Rate performance as attached Figure 1 As shown; The specific data of peel strength performance are listed in Table 1.

[0048] Table 1: PI adhesive material composition and electrode peel strength performance sample Structural composition (molar percentage) Halloysite nanotube content, wt% Peel force / N Example 1 BTDA:6FBAB / 2SON=100:100 0 23.91 Example 2 BTDA:6FBAB / 2SON =100:100 10 29.43 Example 3 6FDA:BTDA:ODA:6FBAB / 2SON=80:20:80:20 0 12.37 Example 4 6FDA:BTDA:ODA:6FBAB / 2SON=80:20:80:20 10 17.25 Example 5 ODPA:BTDA:TFMB:6FBAB / 2SON=70:30:70:30 0 11.85 Example 6 ODPA:BTDA:TFMB:6FBAB / 2SON=70:30:70:30 10 16.74 Comparative Example 1 PVDF 0 6.93 Comparative Example 2 CMC 0 7.21 From the data in Table 1, it can be seen that compared with Comparative Examples 1 and 2, Examples 1 and 2 using the fluorine-containing soluble polyimide adhesive of the present invention as the adhesive material have higher bonding strengths. At the same time, the bonding effect of Example 2 doped with a small amount of halloysite nanotubes is better than that of Example 1. Figure 1 It can be seen from the data that the rate performance of the silicon negative electrode lithium ion battery using the fluorine-containing soluble polyimide of the present invention as a binder is better, and the battery performance of the PI doped with halloysite nanotubes is also relatively improved.

[0049] It can be seen that the fluorine-containing soluble polyimide adhesive material proposed in the present invention has excellent rate performance in silicon negative electrode lithium ion batteries, is simple to operate, and does not produce by-products. This implementation scheme has good industrial prospects.

[0050] Finally, the method of the present invention is only a preferred embodiment and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A fluorine-containing soluble polyimide adhesive for lithium batteries, wherein the fluorine-containing polyimide is prepared by reacting dianhydride and diamine, characterized in that: The dianhydride includes 3,3',4,4'-benzophenone tetracarboxylic dianhydride, the diamine includes 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, wherein the structure of the fluorinated polyimide is as shown in Formula I: , Wherein, groups A and B are independently selected from or , and A and B are different.

2. The fluorinated polyimide binder according to claim 1, characterized in that: The dianhydride also includes other dianhydrides, and the diamine also includes other diamines. The other dianhydrides are selected from at least one of 3,3',4,4'-biphenyltetracarboxylic dianhydride, polyphthalic anhydride, 4,4'-oxydiphthalic anhydride and 4,4'-hexafluoroisopropylphthalic anhydride; the other diamines are selected from at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine and 2,2'-bis(trifluoromethyl)diamino.

3. The fluorinated polyimide binder according to claim 1, characterized in that: The dianhydride is 4,4'-hexafluoroisopropylphthalic anhydride and 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and the diamine is 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 4,4'-diaminodiphenyl ether.

4. The fluorinated polyimide binder according to claim 1, characterized in that: The dianhydride is 3,3',4,4'-dibenzophenonetetracarboxylic dianhydride and 4,4'-oxydiphthalic anhydride, and the diamine is 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, and 2,2'-bis(trifluoromethyl)diamino.

5. The fluorinated polyimide binder according to claim 1, characterized in that: The molar percentage of the structure of formula I in the fluorine-containing polyimide binder is 70-100%.

6. The fluorinated polyimide binder according to any one of claims 1 to 5, characterized in that: The binder further comprises an inorganic material, and the inorganic material is selected from inorganic fibers, preferably ilex fibers.

7. A method for preparing the fluorinated polyimide binder according to any one of claims 1 to 6, the method comprising the following steps: (1) Adding dianhydride and diamine to a non-protonic polar solvent for polycondensation to prepare a polyamic acid resin solution; (2) After the polymerization is completed, a catalyst and a dehydrating agent are added, and the reaction is continued by stirring to obtain a sol; (3) Pour the sol into anhydrous ethanol for precipitation.

8. The preparation method according to claim 7, characterized in that: The aprotic polar solvent in step (1) is selected from at least one of N,N-dimethylformamide, N-methylpyrrolidone and N,N-dimethylacetamide.

9. The preparation method according to claim 7, characterized in that: In step (2), the catalyst is selected from at least one of pyridine, isoquinoline and picoline, and the dehydrating agent is acetic anhydride.

10. Use of the fluorinated polyimide adhesive according to any one of claims 1 to 6 or the fluorinated polyimide adhesive prepared by the preparation method according to any one of claims 7 to 9 in the field of lithium-ion batteries, characterized in that: The lithium-ion battery is a silicon negative electrode lithium-ion battery.

Citation Information

Cited By

  • Fluorine-containing soluble polyimide adhesive special for lithium ion battery and preparation method and application of fluorine-containing soluble polyimide adhesive

    CN120137588A

  • Cross-linked polyimide binder for silicon-based negative electrode of lithium ion battery and preparation method of cross-linked polyimide binder

    CN120442211A

  • Low-dielectric polyimide film material as well as preparation method and application thereof

    CN120647941A